Дослідження впливу протипухлинних вакцин на основі курячих ембріональних білків та білоквмісних метаболітів Bacillus subtilis B-7025 на клітинну ланку імунітету у мишей з карциномою легені Льюїс - Грегірчак, Наталія Миколаївна; Бабій, О. П.; Шпак, Є. Г. (My University, 2012)
На моделі карциноми легені Льюіса вивчали протипухлинну активність ксеногенних і гомологічних вакцин виготовлених на основі білоквмісних продуктів життєдіяльності Bacillus subtilis В-7025 з молекулярною масою 18,5 та 70 кДа. Був виявлений зв'язок між динамікою росту пухлин у мишей, імунізованих препаратами вакцин, та цитотоксичною активністю лімфоцитів та макрофагів. Research of influence of anticancer vaccines based on chick embryonic proteins and protein containing metabolites Bacillus subtilis B-7025 on cellular immunity in mice with Lewis lung carcinoma Antitumor activity of xenogeny and homologous vaccines prepared with the use of protein containing metabolites of Bacillus subtilis B-7025 with molecular weight 18.5 and 70 kDa were studied on Lewis lung carcinoma. The relation of tumour growth dynamics in mice that received vaccines injections with cytotoxic activity of lymphocytes and macrophages was revealed. It is shown that the most effective vaccine in influencing cellular fraction of the immune system operated mice with Lewis lung carcinoma wasthe one based on chicken embryonic protein and metabolite B.subtilis B-7025 with molecular weight 70 kDa. Those results can be used for further studies of the impact on humoral immunity and for potential production of anticancer vaccines based on glycoproteins and chicken embryonic proteins.
Keywords: ад'ювант; протипухлинні аутовакцини; карцинома; проліферація; adjuvant; cancer vaccines; proliferation; кафедра біотехнології і мікробіології